2021
DOI: 10.1111/evj.13500
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of ACTH as a biomarker for pituitary pars intermedia dysfunction in horses: A systematic review and meta‐analysis

Abstract: Background: Accuracy of baseline ACTH for the diagnosis of PPID in horses varies between studies.Objectives: To estimate the diagnostic accuracy of ACTH as a biomarker for PPID in adult horses and appraise potential causes of heterogeneity. Study design: Systematic review and meta-analysis.Methods: A literature review identified studies reporting diagnostic accuracy data for extraction. Risk of bias was evaluated using QUADAS-2. Two random-effects models, the hierarchical summary receiver operating curve (HSRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…PRISMA provides several resources, including a checklist and a template flow diagram for reporting results to structure the systematic review. Once selected studies are identified, quality of evidence can be assessed using a range of methodologies, including GRADE, JBI and QUADAS 7,8,10 . These provide a structured framework to evaluate the study design, population, methodology and analysis of each included publication.…”
Section: Type Of Review (Methodology Examples) Advantages Disadvantagesmentioning
confidence: 99%
See 4 more Smart Citations
“…PRISMA provides several resources, including a checklist and a template flow diagram for reporting results to structure the systematic review. Once selected studies are identified, quality of evidence can be assessed using a range of methodologies, including GRADE, JBI and QUADAS 7,8,10 . These provide a structured framework to evaluate the study design, population, methodology and analysis of each included publication.…”
Section: Type Of Review (Methodology Examples) Advantages Disadvantagesmentioning
confidence: 99%
“…They aim to collate and analyse all the current evidence on a specific area. 7,8 The stages involved include formulating a review question, defining search criteria, defining inclusion and exclusion criteria, developing and registering a protocol, conducting a systematic search of databases, reviewing and identifying studies for inclusion, documenting reasons for exclusion, assessing quality of studies, extracting data, analysing and synthesising data and drawing conclusions. They usually have more than one researcher duplicating methodology to increase the reliability and validity of findings.…”
mentioning
confidence: 99%
See 3 more Smart Citations